Enhancing the nutritional value of cold-pressed oilseed cakes through extrusion cooking. (May 2022) - Vidal, Natalia P.; Roman, Laura; Swaraj, V.J. Shiva; Ragavan, K.V.; Simsek, Senay; Rahimi, Jamshid; Kroetsch, Benjamin; Martinez, Mario M.
Abstract: The most abundant oilseed cakes, soybean, rapeseed/canola, and sunflower, and especially those from cold-pressing, contain meaningful amounts of antinutritional polyphenols that limit their potential as plant protein sources. The objective of this study was to remove polyphenols, and especially sinapic and chrologenic acid derivatives in canola and sunflower, respectively, using pilot-scale extrusion, and without compromising the nutritional and the technological quality of the protein fraction. Extrusion significantly increased the ratio of soluble to insoluble dietary fiber from 0.45 to 0.58 in canola and from 0.19 to 0.31 in sunflower, whereas the opposite was found in soybean (0.52 to 0.36). Canola (67.7 mg GAE/g) and sunflower (58.9 mg GAE/g) exhibited large quantities of polyphenols, which mostly consisted of sinapic and chlorogenic acid derivatives, respectively. Extrusion increased the proportion of free polyphenols and did not significantly reduce the amount of sinapic acid derivatives in canola. On the contrary, extrusion decreased the content of free polyphenols in sunflower by 68%. Generally, the extrusion conditions shown in this study resulted in limited protein denaturation and aggregation and a moderate decrease in β- sheet structures (up to 59%), which led to similar liquid holding capacity and enhanced protein solubility. Extrusion notably increased the gastric protein hydrolysis of soybean cake, but it negligibly affected that of canola and sunflower counterparts, possibly due to the counteracting effect of indigestible quinone-protein adducts. Extrusion is a promising technology to reduce polyphenols meaningfully in certain oilseed cakes while retaining or improving protein quality. Highlights: Cold-pressed cakes were rich in antinutritional polyphenols Extrusion increased the soluble dietary fiber content in canola and sunflower cakes Extrusion decreased the content of free polyphenols in sunflower by 68% Extrusion resulted in limited protein aggregation and enhanced solubility Extrusion is promising to reduce polyphenols while retaining protein quality